PENERBITAN KARTU TANDA PENDUDUK BERBASIS NOMOR INDUK KEPENDUDUKAN SECARA NASIONAL DI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA PADANG - Arnes Satriani dan Ahmad Deni (Fakultas Hukum Universitas Tamansiswa Padang, 2018)
Article 1 number 14 of Act Number 23 of 2006 concerning Population Administration, states that the Identity Card (KTP) is the official identity of the population as self-proof issued by the Implementing Agency applicable in the entire territory of the Unitary State of the Republic of Indonesia. But often ID cards are misused in their use, for example, among others: hiding identity (terrorists) and manipulating ID cards for elections. For this reason, a more orderly population administration system is needed by using an Electronic Population Identity Card (e-KTP), which is a new method adopted by the government by building a population database nationally to provide identity to the public. Electronic Identity Card, hereinafter abbreviated as KTP-el, is a Citizen Identity Card equipped with a chip which is the official identity of the population as self-proof issued by the Implementing Agency. This is regulated in Presidential Regulation Number 35 of 2010 concerning Amendment to Presidential Regulation Number 26 of 2009 concerning Application of National Identity Cards Based on National Population Number. Residents who have received National Identity Cards based on the Population Identity Number in Padang City amounted to 13.40 percent of the total population who had recorded. The obstacles are the unavailability of blanks from the center so that the Issuance of Identity Cards Based on the Population Registration Number does not run smoothly. The efforts made by the Padang City Population and Civil Registry Service to resolve the above problems are by issuing a Recording Certificate which serves as a substitute for the temporary Population Identity Card which has a validity period of 6 (six) months and can be extended until the National Identity Card Based The Population Master Number is published.